Effect of hydrogen peroxide topical application on the enamel and composite resin surfaces and interface - Dutra Rodrigo; Branco Jose; Alvim Hugo; Poletto Luiz; Albuquerque Rodrigo (Wolters Kluwer Medknow Publications, 2009)
Objectives: The objective of the present study was to analyze the superficial roughness and the interface between enamel and composite resin restorations after dental bleaching procedure. Materials and Methods: Black′s class V cavities were made and restored with composite resin, and the whole set, enamel-restorative material, was treated with 35% hydrogen peroxide. Seven procedures of 30 min each were performed. A profilometric assessment was carried out before and after the treatment of each sample, and roughness scores were obtained. Treated and untreated samples were analyzed under scanning electronic microscope and images of their surface were obtained. Results and Conclusion: The treatment with 35% hydrogen peroxide caused no alteration in the interface between enamel and composite resin, Tetric Ceram, fillings and the topical application of 35% hydrogen peroxide on enamel and composite resin, Tetric Ceram, caused an alteration of their surface topography, featuring a predominance of depressions after the bleaching treatment.